The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.53850/joltida.1087377
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship between College Students’ Cyberbullying Awareness and Ability to Ensure their Personal Cybersecurity

Abstract: The purpose of this study is to examine the relationship between college students’ cyberbullying awareness and their ability to ensure their personal cybersecurity. A total of 401 students participated in this study. The Ability to Ensure Personal Cybersecurity Scale, the Cyberbullying Awareness Scale, and a Personal Information Form developed by the researcher were all used during data collection. A relational screening model was used in this study. Also, an unpaired t-test, one-way analysis of variance (ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…First of all, it was concluded that there was no significant difference between the thoughts of students studying in different types of secondary schools about cyberbullying behaviors. It can be said that this result is in parallel with the results of many studies conducted in the field (Patchin & Hinduja, 2006;Williams & Guerra, 2007;Topçu, Erdur-Baker & Çapa-Aydın, 2008;Arıcak, 2009;Türk & Gürkan, 2019;Zorlu, 2023). However, in studies conducted in the field, bullying (or cyberbullying) is generally handled depending on the gender variable, and accordingly, it is seen that male students have more bullying behaviors or tendencies (Boulton & Underwood, 1992;Ahmad & Smith, 1994;Li, 2007;Topçu et al, 2008;Satan, 2010;Serin, 2012;İskender, 2013;Pekşen Süslü & Oktay, 2018).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 56%
“…First of all, it was concluded that there was no significant difference between the thoughts of students studying in different types of secondary schools about cyberbullying behaviors. It can be said that this result is in parallel with the results of many studies conducted in the field (Patchin & Hinduja, 2006;Williams & Guerra, 2007;Topçu, Erdur-Baker & Çapa-Aydın, 2008;Arıcak, 2009;Türk & Gürkan, 2019;Zorlu, 2023). However, in studies conducted in the field, bullying (or cyberbullying) is generally handled depending on the gender variable, and accordingly, it is seen that male students have more bullying behaviors or tendencies (Boulton & Underwood, 1992;Ahmad & Smith, 1994;Li, 2007;Topçu et al, 2008;Satan, 2010;Serin, 2012;İskender, 2013;Pekşen Süslü & Oktay, 2018).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 56%
“…Triplett [31] carried out a review study to find out how children's cybersecurity awareness was important, and concluded that the adoption of game-based strategies to increase children's awareness could be effective. Zorlu [32] conducted an empirical study with students of Bartin University, Turkey, and found that college students required awareness to keep themselves protected against cyberbullying and cybersecurity threats. The results highlighted that female students had higher awareness as compared to male students.…”
Section: Cybersecurity and Online Learningmentioning
confidence: 99%
“…The purpose of individuals' computational thinking is to use different algorithms to solve problems and to achieve problem-solving success by using different solution methods. (Korucu et. al., 2017).…”
Section: Extended Summarymentioning
confidence: 99%